2010
DOI: 10.1016/j.energy.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Technoeconomic analysis of a low CO2 emission dimethyl ether (DME) plant based on gasification of torrefied biomass

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 6 publications
0
60
2
Order By: Relevance
“…In this work, the resulting energetic efficiencies are close or even greater than those reported in similar BTL/G assessments [1,15,16]. However, the energetic efficiencies of dedicated DME [38][39][40] and methanol [40,41] production processes are slightly higher than our best biorefinery concept. The lower energetic efficiency obtained in this work is justified by the additional conversion steps necessary to transform DME into derivedproducts.…”
Section: Sensitivity Analysiscontrasting
confidence: 38%
“…In this work, the resulting energetic efficiencies are close or even greater than those reported in similar BTL/G assessments [1,15,16]. However, the energetic efficiencies of dedicated DME [38][39][40] and methanol [40,41] production processes are slightly higher than our best biorefinery concept. The lower energetic efficiency obtained in this work is justified by the additional conversion steps necessary to transform DME into derivedproducts.…”
Section: Sensitivity Analysiscontrasting
confidence: 38%
“…Numerous studies concluded that the torrefied biomass can avoid many limitations associated with the raw biomass because it produces moisture free hydrophobic solid products (Acharjee et al, 2011), decreases O/C ratio , reduces grinding energy (Repellin et al, 2010;Phanphanich and Mani, 2011), enhances energy density (Yan et al, 2009), increases bulk density and simplifies storage and transportation (Bergman, 2005;Phanphanich and Mani, 2011), improves particle size distribution (Phanphanich and Mani, 2011), intensifies combustion with less smoke (Pentananunt et al,1990), shifts combustion zone to the high temperature zone in a gasifier (Ge et al, 2013), and increases the resistance to the biological decay (Chaouch et al, 2010). Many of these improvements make the torrefied biomass more suitable than the raw biomass for co-firing in the conventional coal power plants, with minor modifications (Clausen et al, 2010).…”
Section: Motivations For Torrefactionmentioning
confidence: 99%
“…Torrefaction is a partial pyrolysis of biomass which is carried out under atmospheric pressure in a narrow temperature range of 200-300 °C, and under an inert environment (Bergman et al, 2005;Clausen et al, 2010;Medic et al, 2011;Prins et al, 2006). It produces three major products such as dark color solid products, yellowish color acidic aqueous products, and non-condensable gaseous products.…”
Section: Overview Of Torrefactionmentioning
confidence: 99%
“…This CO2 will typically be vented to the atmosphere, but if it was compressed and stored underground (CCS), the complete biorefinery would have the effect of reducing the CO2 content in the atmosphere and would thereby be a climate-mitigating technology. Such a biorefinery is investigated in, e.g., [3,4].…”
Section: Introductionmentioning
confidence: 99%